B44 The missing superior trunk. (11th August 2022) - Costa, F; Scaduto, V; Pascarella, G; Strumia, A; Remore, LM; Longo, F; Gargano, F; Sammartini, E; Sammartini, D; Tognù, A; Agrò, FE
Abstract : Background and Aims: The brachial plexus is a complex anatomical structure and its variability is frequently observed. [1] Some rare arrangements of the plexus might represent a challenge even for experts in regional anesthesia. Ultrasound scanning gave us the chance to identify and illustrate a very rare variant of the brachial plexus, never described so far ( figure 1 ) Methods: A 29-year-old female resident was selected as a model for a live demonstration regarding ultrasound guided regional anesthesia. Results: Scanning on the right side of the neck:C5 – emerges between anterior and posterior tubercles of C5 transverse process (TP); courses anteriorly to the anterior scalene muscle (ASM), then becoming superficial, goes back, and dives into the interscalene groove alone without joining the C6 root.C6 and C7 – emerge from the corresponding TP, run inside the interscalene groove, joining each other below the transverse cervical artery (TCA), forming a sort of trunk. C8 – becomes visible in the corner pocket and immediately joins the trunk. T1 – never becomes visible TCA level: C5 root and the trunk are clearly visible; a fascial sheet keeps them divided. ( figure 2 ) (The course of the plexus is visible in a video linked to the qr code in the figure.) The contralateral plexus was perfectly normal. Conclusions: This rare anatomical variation might represent a challenge in case of interscalene block. Since the upper trunk does not exist, a superior trunk block (STB) [3] would be impossible. An accurate ultrasound examination, aiming to recognize standardized structures [2] would be helpful.